Digital Literacy: Learning Culture in the Era of Revolution 5.0 Islamic Primary School - Rina Rahmi; Maya Agustina; Tengku Hafinda; Suzana (Universitas Pendidikan Ganesha, 2026)
Literacy is an important requirement in the fifth industrial revolution to ensure lifelong learning independence in the information and digital age. To that end, this study aims to examine Digital Literacy: Learning Culture in the 5.0 Revolution Era of Islamic Elementary Schools. The subjects of this study are school principals, head teachers, teachers, and students of Islamic Elementary Schools (SRI). This study employs a qualitative approach using the Grounded Theory method. Data collection techniques include observation, interviews, and documentation. Data analysis techniques utilize data triangulation. The results of the study indicate that the literacy culture implemented by SRI has a positive impact on students' cognitive development, both in terms of digital skills and the learning process. Learning that utilizes digital technology has revolutionized traditional learning methods by opening new opportunities for students to hone their skills and knowledge. Additionally, students' ability to find, evaluate, and create information through digital means has become increasingly crucial in today's digital age. Through guidance from teachers and digital literacy programs, students are taught to independently seek information using a critical approach. Students are trained to evaluate information based on its source, validity, and reliability. Furthermore, the ability to create digital content such as presentations and videos is also part of developing 21st-century skills.